2020
DOI: 10.3758/s13414-020-02079-y
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropies of tactile distance perception on the face

Abstract: The distances between pairs of tactile stimuli oriented across the width of the hand dorsum are perceived as about 40% larger than equivalent distances oriented along the hand length. Clear anisotropies of varying magnitudes have been found on different sites on the limbs and less consistently on other parts of the body, with anisotropies on the center of the forehead, but not on the belly. Reported anisotropies on the center of the forehead, however, might reflect an artefact of categorical perception from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 89 publications
(161 reference statements)
1
10
0
Order By: Relevance
“…In contrast, our results indicate the presence of a reversed anisotropy (with along distances feeling bigger than across ones) on the lower back, consistent with the recent report of Plaisier et al (2020). Qualitatively similar anisotropies of tactile distance have been reported on a range of body parts beside the hand dorsum, including the palm (Fiori & Longo, 2018;Longo, 2020;Longo et al, 2015), the forearm (Green, 1982;Le Cornu Knight et al, 2014), the thigh (Green, 1982;Tosi & Romano, 2020), the shin (Stone et al, 2018), the face (Fiori & Longo, 2018;Longo et al, 2015Longo et al, , 2020, and the upper back (this study). While several studies have failed to find any anisotropy at all on the belly (Green, 1982;Longo et al, 2019;Marks et al, 1982), to our knowledge, the lower back is the first body part in which a reversed anisotropy is present.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, our results indicate the presence of a reversed anisotropy (with along distances feeling bigger than across ones) on the lower back, consistent with the recent report of Plaisier et al (2020). Qualitatively similar anisotropies of tactile distance have been reported on a range of body parts beside the hand dorsum, including the palm (Fiori & Longo, 2018;Longo, 2020;Longo et al, 2015), the forearm (Green, 1982;Le Cornu Knight et al, 2014), the thigh (Green, 1982;Tosi & Romano, 2020), the shin (Stone et al, 2018), the face (Fiori & Longo, 2018;Longo et al, 2015Longo et al, , 2020, and the upper back (this study). While several studies have failed to find any anisotropy at all on the belly (Green, 1982;Longo et al, 2019;Marks et al, 1982), to our knowledge, the lower back is the first body part in which a reversed anisotropy is present.…”
Section: Discussionsupporting
confidence: 92%
“…It is not clear whether the body midline functions as a categorical boundary in this way, though studies have found localization biases in the direction of the spine (Cholewiak et al, 2004;van Erp, 2005). One recent study compared tactile distance judgements for stimuli crossing the face midline on the forehead compared to the left or right side of the forehead, finding no evidence for any categorical effect of the face midline (Longo et al, 2020). It is possible, however, that the presence of the spine may make the midline more salient on the back.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its efficacy for the treatment of FHD has been investigated in only two patients thus far. 11,12 Therefore, we prospectively ---------------------------------------------------------…”
Section: Introductionmentioning
confidence: 99%
“…1A). 4,[7][8][9][10][11] Recently, a paradigm has been developed that allows testing of tactile spatial perception across 8 orientations to provide a more accurate estimation of RF size, shape, and orientation. 7 Indeed, perceptual distortions of tactile space match cortical tactile space organization in the primary somatosensory cortex.…”
mentioning
confidence: 99%